Enduring benefits of exercise after spinal cord injury: Insights from a case study - Candace Vermaak; Lovemore Kunorozva (African Journal of Disability, 2025)
Introduction: Spinal cord injuries (SCIs), while relatively rare, profoundly alter the lives of those affected. Among the diverse causes of SCI, traumatic sporting injuries represent 8.7% of newly reported cases. Despite the life-altering consequences of SCI, physical activity (PA) can mitigate some of these impacts.